2008
DOI: 10.1039/b809022j
|View full text |Cite
|
Sign up to set email alerts
|

Henry constant and isosteric heat at zero-loading for gas adsorption in carbon nanotubes

Abstract: The Henry constant and the isosteric heat of adsorption at zero loading in a carbon nanotube bundle are studied with Monte Carlo integration for the adsorption of gases over a range of temperatures. The spacing between nanotubes in a bundle is determined from the minimization of potential energy of interaction between these tubes. We study different tube configurations with bundles of 2, 3, 4 and 7 tubes. Depending on the configuration it is found that the spacing is of between 0.31 to 0.333 nm, and this falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…The question that one has to raise is: how would one benefit from this accessible volume, should we decide to use it? Do et al (2008bDo et al ( , 2008c have shown that by using the accessible volume the Henry constant is always positive (which should be the case if one would expect it to have physical significance). The surface excess of adsorption of argon on a graphitic surface is calculated from:…”
Section: Accessible Volumementioning
confidence: 95%
See 2 more Smart Citations
“…The question that one has to raise is: how would one benefit from this accessible volume, should we decide to use it? Do et al (2008bDo et al ( , 2008c have shown that by using the accessible volume the Henry constant is always positive (which should be the case if one would expect it to have physical significance). The surface excess of adsorption of argon on a graphitic surface is calculated from:…”
Section: Accessible Volumementioning
confidence: 95%
“…Details of this analysis are given in Do et al (2008cDo et al ( , 2008dDo et al ( , 2008e, 2009. For a given volume, , containing solid atoms and void space in which adsorption is taking place, the interaction energy between a fluid particle placed at a point r and all solid atoms be 蠁(r).…”
Section: Accessible Volumementioning
confidence: 98%
See 1 more Smart Citation
“…It is known that helium adsorbs, especially in pores of molecular dimensions, and if its adsorption is neglected the gas phase volume is over estimated. This overestimation could compromise the determination of the Henry constant and isosteric heat (Do et al 2008b(Do et al , 2008c.…”
Section: Accessible Pore Volumementioning
confidence: 97%
“…In simulation, the intrinsic Henry constant can be defined as the ratio of the excess amount to the bulk gas density, which is given by [117][118][119] :…”
Section: Henry Constantmentioning
confidence: 99%